Analysis of Medical Record Complete Flexibility to Complete Claims of Health BPJS RS Baptis Kota Batu - Oktoriani, Ervita Nindy; Sutrisno, Joko; Mayasari, Ema; Sodik, Muhammad Ali (Journal of Global Research in Public Health, 2018)
The completeness of the inpatient medical record file is one of the requirements of BPJS claims that will affect BPJS claim settlement process. This study aims to determine the relation of the completeness of the medical record file to the settlement of BPJS hospitalization claim at Baptist Hospital Batu City. The research method used the type of Descriptive Analytic and Random Sampling data collection with sampling technique that is Random Sampling and obtained sample of 191 data of Inpatient Patient. By using the Co-efficient Controvency test. The results of the study showed that the level of completeness of the medical records records were 161 (84.3%) and 30 (15.7%) incomplete medical record files, the claimed claims level of 161 (84.3%) and 30 (15,7%) file has pending claims. Based on the result of statistical test of coefficient of contigency there is influence of file beam to settlement of claim = 0,000 <Î± (0,05)), then reject H0. It is necessary to have the policy of the doctor in charge of each installation, it is necessary to socialize to the doctor of DPJP to better understand the importance of medical record usage and improve the coordination and communication between the nurse and doctor DPJP.